Acceptance Factors of Generative AI in EFL Teaching: A Pedagogical Perspective - Talal Alasmari (STKIP Singkawang, 2024)
The emergence of generative artificial intelligence (GenAI) has brought abundant potentials and challenges to the educational sector. This study explores the acceptance and adoption of GenAI in English language and its pedagogical affordability for EFL instructors in tertiary level institutions in the Kingdom of Saudi Arabia. An exploratory sequential mixed method was utilized in this study to gain in-depth insights into the quantitative findings. The first quantitative phase recruited 256 EFL instructors in Saudi Arabia while the follow-up qualitative phase incorporated 17 interviewees. The findings of this study indicate that anthropomorphism, trust, ethics and regulations, and pedagogical affordability are significant determinants of instructors’ acceptance of GenAI. Conversely, instructors’ acceptance was not significantly influenced by communication capability of GenAI. Yet, there was no evidence of significant differences in GenAI acceptance or adoption due to demographic variables such as gender, age, and degree. The pedagogical affordances of GenAI appears to be the most acceptance factor specifically the productivity and efficiency that GenAI afford for instructors. The study recommends establishing ethical guidelines and embracing transparency and accountability to maintain academic integrity.